Angiolymphoid hyperplasia with eosinophilia mimicking multiple cylindromas: a rare case report - Sheikh Manzoor Ahmad; Gh Mohiuddin Wani; Bilquees Khursheed; Seema Qayoom (Wolters Kluwer Medknow Publications, 2014)
Angiolymphoid hyperplasia with eosinophilia (ALHE) is a rare and idiopathic vascular disorder. It is characterized by red to brown papules and nodules, typically localized on the head and neck, particularly around the ear as singular or multiple lesions. Although ALHE is a benign disease, lesions are often persistent and difficult to eradicate. Young to middle age women are more commonly affected. The histological examination corresponds to a florid vascular proliferation with atypical endothelial cells surrounded by a lymphocytic and eosinophilic infiltrate. We describe an elderly male with multiple nodular lesions over the scalp mimicking cylindromas; the histological examination was consistent with ALHE.